Complex modulation of fingertip forces during precision grasp and lift after theta burst stimulation over the dorsal premotor cortex - Drljačić, Dragana; Pajić, Sanja; Nedeljković, Aleksandar; Milanović, Sladjan D; Ilić, Tihomir V (Vojnosanitetski pregled, 2017)
Background/Aim. Adaptive control and fingertip force synchronization of precise grasp stability during unimanual manipulation of small objects represents an illustrative example of highly fractionated movements that are foundation of fine motor control. It is assumed that this process is controlled by several motor areas of the frontal lobe, particularly applicable to the primary motor (M-1) and dorsal premotor cortex (PMd). Aiming to examine the role of PMd during fine coordination of fingertip forces we applied theta burst repetitive magnetic stimulation (TBS) to disrupt neural processing in that cortical area. Methods. Using a single-blind, randomized, crossover design, 10 healthy subjects (29 ± 3.9 years) received single sessions of continuous TBS (cTBS600), intermittent TBS (iTBS600), or sham stimulation, separate from one another at least one week, over the PMd region of dominant hemisphere. Precision grasp and lift were assessed by instrumented device, recording grip (G) and load (L) forces, during three manipulation tasks (ramp-and-hold, oscillation force producing and simple lifting tasks), with each hand separately, before and after interventions. Results. We observed the improvement of task performance related to constant error (CE) in oscillation task with the dominant hand (DH) after the iTBS (p = 0.009). On the contrary, the cTBS reduced variable error (VE) for non-dominant hand (NH), p = 0.005. Considering force coordination we found that iTBS worsened variables for NH (G/L ratio, p = 0.017; cross-correlation of the G and L, p = 0.047; Gain, p = 0.047). Conclusion. These results demonstrate the ability of TBS to modulate fingertip forces during precision grasping and lifting, when applied over PMd. These findings support the role of PMd in human motor control and forces generation required to hold small objects stable in our hands.
Keywords: motor cortex; transcranial magnetic stimulation; hand strength